Estratrégias empresariais no setor avícola: estudo comparativo de duas regiões produtoras - Matos, Vitor Alberto (1996)
This thesis treats two themes very relevant: the strategic process faced by leader firms of poultry producer segment since the eighties and the possibility of emergent firms of regions which experienced intense developrnent processes to catch up tecnological frontier from specific 'windows of opportunity'. The idea to be developed is to compare the conditions of ernergence and development of poultry industries in the South region with those which initiated the implantation of poultry projects in the Mato Grosso do Sul region. This research encompass two main questions: the first anlyses the transformations occurred in the regional structure in consequence of firms'strategic actions; the second is related to the possibilities of regional firms to foIlow the evolution and the growth of the Jeaders. The fundamental element of analysis is the technology. The purpose of the analysis is to explain the set of strategies used to deal with the competition processo The rnain hypothesis is that, during the process of its constitution, Brazilian poultry industry firms has used a dependent-imitative strategy and changed for another of defensive type strategy over the years and as long as they increase their ability to incorporate technical progresso Two other sub-hypotheses are also very significant. The fírst one is to verify that strategic changes intended to give more productive flexibility, giving rise to differentiated firms, settled in regions characteristicly disparate, resuJted from strong economic and social asymmetries. The second one tries to show that the conditions of emergence of leader firms existing Ui the South region repeated in the Centre-West, associated to abundant stocks of agricultural inputs and to powerful mechanisms of Governrnent incentives. In sum, the thesis discusses the more important inovative strategies for the constitution of technological and productive park of westem Santa Catarina, the possibilities of these strategies to be repeated in the Centre- West, the reasons of the expansion of leader firms, the possibilities of transfer of technology and adoption of strategies among the more dynamic enterprise groups and the emergents, the competitive elements which could constitute in ''windows of opportunity' that allow the growth of local firms and the impact of this transfer of technology on learning and profitability of integrated rural production segment.